The molecular basis of insulin action - White, Morris (Henry Stewart Talks, 2007)
Mechanisms to diabetes, The insulin response, Growth factor receptor tyrosine kinases, The insulin receptor, The substrate hypothesis of insulin action, The family of Irs-proteins, The insulin signaling cascade, Role of the Irs2 signaling system